ANALISIS KINERJA KEUANGAN PADA KOPERASI UNIT DESA TANI BAHAGIA DESA KULIM JAYA LUBUK KABUPATEN INDRAGIRI HULU - Fitri Agustiyana; Gusnardi Gusnardi; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine how the financial performance of the unit cooperative Desa Tani Bahagia Desa Kulim Jaya Indragiri Hulu Regency seen from the ratio of solvency, profitability and liquidity. This type of research is descriptive quantitative. The data collection technique in this study was taken from the cooperative financial statements from 2013 to 2015 and used in this study is the ratio analysis based on the Peraturan Menteri Negara Koperasi dan Usaha Kecil dan Menengah Nomor: 20/Per/M.KUKM/XI/2009.. The percentage of liquidity is in the Unhealthy category with a percentage value of <174%, amounting to 99.39% - 166.78%. The solvency percentage got the Very Unhealthy category with a percentage of <100%, amounting to 94.74% - 80.67%. The percentage of profitability is categorized as Very Healthy with a percentage value of> 10%, amounting to 0.23% - 22.80%. So it can be concluded that the financial performance of the unit cooperative Desa Tani Bahagia Desa Kulim Jaya Indragiri Hulu Regency, seen from the analysis of liquidity ratios, solvency and profitability, shows a condition that tends to decline.Key Words: Liquidity, Solvability, Rent Ability